Persepsi Alkitab Mengenai Eskatologi Khususnya Dalam PL - Ekhat Binti Patangun; Aprianus Moimau (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The Welhausen group teaches that eschatology is a concept that first appeared before the current post-exilic era. Many Bible scholars admit that the concept of God is closely related to the history of the salvation of the Israelites and gives them eschatological hope. The vision of eschatology in the Old Testament is a unique phenomenon that occurred in the Israeli nation and is not found outside of Israel because eschatology did not appear in religious communities that doubted God's guidance. Eschatology is the religious belief of the Israeli people which grew from their faith in God who provided salvation for their people